Performativity in the Gallery Staging Interactive Encounters - Bullen, J. Barrie; Remes, Outi; MacCulloch, Laura; Leino, Marika (Peter Lang AG, Internationaler Verlag der Wissenschaften, 2013)
This book coincides with an increase in the programming of live art elements in many galleries and museums. Traditional art history has, however, been wary of live art's interdisciplinarity and its tendency to encourage increased formal and conceptual risk taking. Time-based performances have challenged the conventions of documentation and the viewer's access to the art experience. This book questions the canon of art history by exploring participation, liveness, interactivity, digital and process-based performative practices and performance for the camera, as presented in gallery spaces. The essays present both academic research as well as case studies of curatorial projects that have pushed the boundaries of the art historical practice. The authors come from a wide range of backgrounds, ranging from curators and art producers to academics and practising artists. They ask what it means to present, curate and create interdisciplinary performative work for gallery spaces and offer cutting-edge research that explores the intricate relationship between art history, live and performing arts, and museum and gallery space.
Keywords: prezentace uměleckého díla; dějiny umění; muzea umění; presentation of art; history of art; art museums; elektronické knihy; electronic books